Palladium-Catalyzed Asymmetric Allylic Alkylation Reaction of 2-Monosubstituted Indolin-3-ones - Chen, Tie-Gen; Fang, Ping; Hou, Xue-Long; Dai, Li-Xin (Synthesis, 2015)
An efficient and practical method was developed for the synthesis of 2,2-disubstituted indolin-3-ones by palladium-catalyzed asymmetric allylic alkylation. Enantioselective construction of quaternary carbon centers was also realized in this way.
Keywords: palladium; allylic substitution; asymmetric catalysis; indolines; quaternary carbon